The cover news reporting in Spain: historical evolution of sources, agenda and frames (1980-2010) - López-Rabadán, Pablo; Casero Ripollés, Andreu (Historia y Comunicación Social, 2014)
In news coverage, the cover of press reference represents a very important subject of study. From a longitudinal analysis, the aim of this article is to examine the evolution of three crucial journalistic issues: sources management, media agenda composition, and dominant framing type. After analyzing a sample of 800 news, results indicate a progressive increase in the number and diversity of sources; an agenda rather static and traditional; and a framing pattern characterized by conflict and balance between the thematic and episodic.
Keywords: Journalistic information; Press reference; Historical evolution; News sources; Media Agenda; Interpretive frame.